Financial literacy, financial knowledge, and financial attitudes as antecedents of financial management behavior - Dityarukmana, Ferdian (Journal of Management and Business Insight, 2025)
Purpose-Financial management issues challenge business actors, such as micro, small, and medium enterprises. A lack of understanding of financial concepts impacts business sustainability. This study analyzes the influence of financial literacy, financial knowledge, and financial attitudes on financial management behavior among micro, small, and medium enterprises. Design/Methodology/Approach-This study uses a quantitative approach with a survey method using questionnaires. The sampling technique was purposive, and 150 respondents from micro, small, and medium culinary businesses in Bantul, Yogyakarta, Indonesia were obtained. The data analysis technique was multiple linear regression using SPSS version 25 statistical tools. Findings-The results showed that financial literacy had a positive but insignificant effect on financial management behavior, so the first hypothesis was rejected. Financial knowledge and financial attitudes each positively affected financial management behavior, so the second and third hypotheses were accepted. Research limitations/implications-This study has limitations in terms of the number of respondents and geographical coverage, which only includes micro, small, and medium-sized culinary businesses in Bantul, Indonesia, so the results cannot be generalized to all companies in other regions. Future research should expand the scope and number of respondents to produce more comprehensive findings. Originality/value-This study focuses on micro, small, and medium enterprises in the culinary sector in Bantul, Indonesia. No similar research has been conducted previously. Previous studies have focused on micro, small, and medium enterprises in the service and fashion sectors. This study also suggests the government's role in supporting financial management behavior for business actors by conducting financial training.